Representations of Tolerance Values in Na Willa: A Conventional Content Analysis for Early Childhood Character Education - Sayyidah Nafisah Hanum (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: Tolerance is an essential component of character education in early childhood because it supports children’s ability to appreciate differences, respect others, cooperate, empathize, and resolve conflicts peacefully. However, the cultivation of tolerance in early childhood requires learning resources that present character values through meaningful and relatable experiences. Children’s films can serve as an audiovisual learning resource by presenting moral and social values through narratives, dialogues, character interactions, and everyday situations that are accessible to young children.Aims and scope of paper: This study aimed to analyze the representation of tolerance values in the film Na Willa and to examine its potential contribution as a learning resource for early childhood character education.Methods: This study employed a qualitative approach using conventional content analysis with an inductive coding process. Data consisted of dialogues, scenes, character interactions, and events in the film that represented tolerance values. Data were collected through repeated observation and documentation of the film. The analysis involved open coding, categorization of similar codes, and thematic interpretation to identify recurring patterns and conceptual categories related to tolerance.Results: The findings identified five major tolerance values represented in Na Willa, namely appreciating differences, respecting others’ opinions, cooperation, empathy, and peaceful conflict resolution. These values emerged from recurring representations in dialogues, character behaviors, interpersonal interactions, and conflict-resolution scenes. The identified representations demonstrate that the film conveys tolerance not only through explicit dialogue but also through characters’ behaviors and social interactions. The findings suggest that Na Willa provides meaningful and contextual representations of tolerance that can potentially be incorporated into early childhood character education through guided viewing and teacher-facilitated discussion.Contribution: This study contributes to the literature on early childhood character education and audiovisual learning by providing a systematic analysis of tolerance representations in a children’s film. It also highlights the potential of culturally relevant film narratives as supplementary learning resources for introducing and strengthening tolerance values among young children.